Higher Degrees of Recanalization after Mechanical Thrombectomy for Acute Stroke Are Associated with Improved Outcome and Decreased Mortality: Pooled Analysis of the MERCI and Multi MERCI Trials - Fields, J.D.; Lutsep, H.L.; Smith, W.S. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Although the combined end point of partial and complete recanalization is a well-established predictor of good outcome following acute stroke intervention, few investigations have evaluated the effect of the degree of recanalization. We hypothesized that greater degrees of recanalization would be associated with a higher likelihood of favorable functional outcomes. MATERIALS AND METHODS: Data from MERCI and Multi MERCI—prospective single-arm trials of endovascular mechanical thrombectomy for acute stroke—were pooled. The TIMI score was used to define the degree of recanalization, and a favorable outcome was defined as an mRS score of 0–2 at 90 days. RESULTS: A total of 305 patients were included. Age, stroke severity, and site of arterial occlusion did not differ among groups stratified by the TIMI score. The unadjusted OR for a favorable outcome increased significantly as the TIMI score increased from 0 to 1 (OR, 5.9; 95% CI, 1.7–20.0; P = .007) and from 2 to 3 (OR. 2.3; 95% CI, 1.2–4.5; P = .01) and the likelihood of death decreased significantly as the TIMI score increased from 2 to 3 (OR, 2.2; 95% CI, 1.1–4.3; P = .05). In multivariate analysis, each increase in TIMI grade increased the odds of a good outcome 2.6-fold (95% CI, 1.9–3.4, P < .0001). CONCLUSIONS: Increases in the TIMI score were highly associated with improved outcomes. This finding not only provides additional evidence that restoration of blood flow improves clinical outcomes in ischemic stroke but also suggests that interventionalists should strive for complete revascularization when they provide endovascular treatment for acute ischemic stroke. CIconfidence intervalIAintra-arterialMERCIMechanical Embolus Removal in Cerebral IschemiamRSmodified Rankin ScaleNIHSSNational Institutes of Health Stroke ScaleORodds ratioPH-2parenchymal hematoma type 2SICHsymptomatic intracranial hemorrhageTIMIThrombolysis in Myocardial Infarction